Production and Application of Monoacylglycerol Product from Coconut Oil in the Processing of Coconut Milk - . Mappiratu; Dedi Fardiaz; Asriani Hasanuddin (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Production of Monoglycerol (MAG) from coconut oil was carried out in a reaction system consisting of coconut oil /glycerol/rice bran/hexane in the ratio of 2 : 0.8 : 10 : 40 (w/w/w/v) and agitate at 300 rpm for 90 hours. The rendement was 85.71% and the product contained 49.80% MAG. Fractination with ethanol 95% increade the MAG content. i.e. 86.50%. The fractination rendement was 49.30%. The fraction did not affect the fatty acid of the MAG. Application of fractionated MAG to preserve coconut milk at 0 and 1.0% of MAG did not affect flavor and colour of he coconut milk. In general the appearance of coconut milk containing MAG was better the coconut milk without MAG. Coconut milk containing 0.75% MAG could be stured at cool and room temperature for 12 weeks without microbiological and physical deftect. Key Word : Monoacylglycerol, rendement, application, coconut milk, fractination.